The Ravello Arabic Epigraph Comes From Ljubuški - Mujić, Muhamed A. (Prilozi za orijentalnu filologiju, 2017)
The purpose of this article is to establish the origin of the Arabic epigraph from an unknown mosque, which is now in the garden of the villa La Casarella in Ravelo. The epigraph was published by Professor Giovanni Oman (Notizie su una iscrizione con caratteri arabi a Ravelle, Annali, Istituto orientale di Napoli, nuova serie XIX, /volume 29, Fascicelo 2, p. 266-268/, and later, after Mm by R. Köbert). The author, on the basis of published as well as unpublished historical sources available to him, has sought to discover the founder of the mosque bearing the epigraph. He has started from the hypothesis of G. Oman who held that the inscription probably originated in Mostar or some other Muslim center in the Balkan Peninsula. In the first part of his article the author publishes the facsimile of the inscription which was part of the work of G. Oman and then presents the text of the inscription in the Arabic script the way he has intel1Preted it himself. This is followed by his translation of the inscription into the Serbo-Croatian language. The text of the inscription itself and its translation into Serbo-Croatian are followed by the author's critical commentary on certain parts of Oman's and Köbert's interpretations and translations of the text of the inscription. Thus, 'certain differences can be noted in this respect between him and the two authors mentioned above. In order to gain insight into the total translation of the inscription text by Oman into Italian and by Köbert into German, the author reproduces their translations in entirety. It is interesting to note that in his research the author has not been able to discover more than three persons bearing the name of Neswh (which appears on the epigraph), otherwise a very common name in the lands under the Ottoman rule, among the founders of mosques in the whole area of the present-day Yugoslavia. One of these men was the second Bosnia governor Nesuh-beg, who in 856 after Hegira erected a mosque in Sarajevo; the second man was Pačadži hadži Nesuh who most probably ereoted his mosque in the first part of the seventeenth century, also in Sarajevo. The third person was a distinguished man from Herzegovina, Nesuh-aga Vučjaković, for whom it is known on the basis of his vaqf-nama, legalized in the third decade of the džumad I 972 that he built two mosques - one in Mostar, another in Ljubuški - but there is no reliable information concerning the years of the erection of these mosques. Because of the fact that we have full names of the first two men and the times of the building of their mosques, the author rejects the possibility that either of these men could have been the founder of the mosque whose inscription bearing the year 966 after Hegira is kept in Ravello. Thus, he has found it necessary to analyses the whole known material concerning the person of Nesuh-aga Vučjaković and his mosques, in order to attempt to solve this interesting case. The analysis which the author has done shows that the Arabic epigraph from Ravello comes from the mosque of Nesuh-aga Vučjaković in Ljubuški and that according to the eyewitness accounts it was taken from that mosque during the Second World War by the officer of an Italian unit during its withdrawal from Ljubuški. In addition, the author points to the fact that the epigraph was engraved by the hand of the same person who did the inscription on the Mostar mosque of Zaim Muhamed-beg, known by the name of Karađoz-beg, in which we find certain elements characteristic for both inscriptions.